A Descriptive Study on the Use of Colloquial Style in English Songs - Endriana Sri Wahyuni (IAIN Salatiga, 2008)
This research is to point out the colloquial styles and the meanings used in English songs. The writer took the data from the text of five cassettes consisting of twenty two English songs. The technique used was the purposive random sampling. The writer presented the data taken from the sample then used a qualitative analysis. The table shows a list of sentences from the sample songs (20 samples from 70 samples) having non Standard English. The findings of this study showed that the characteristics of colloquial style are used in English songs are structural aspect, denotative meanings and connotative meanings.Keywords: Colloquial styles; English songs; structural aspect; denotative meanings and connotative meanings.